Carbon Tax-Aware Optimal Energy Management for Grid-Integrated Parking Facilities with Electric and Fuel Cell Vehicles Supported by PV Generation - Lordoğlu, Merve; Prencuva, Bensu; Taş, Edanur; Tatar, Ayşe Kübra (Firat University Journal of Experimental and Computational Engineering, 2025)
This study addresses the optimal energy management of a grid-connected parking lot integrating photovoltaic (PV) generation, fuel cell electric vehicles (FCEVs) and EVs. The parking area is equipped to meet the charging demands of EVs, and hydrogen is produced for FCEVs via an electrolyzer located within the parking area. Both EV charging power and electrolyzer demand can be met flexibly from the PV system, energy storage system (ESS) or the electrical grid. The objective is to minimize total operational costs while incorporating the impact of carbon taxation. Due to the inclusion of carbon taxes, the proposed optimization framework inherently aims to reduce emissions during vehicle charging and hydrogen production processes. To address the problem, a mixed-integer linear programming-based optimization model is constructed and executed within the GAMS platform. The solution is obtained with the CPLEX solver. Results confirm that the proposed methodology effectively achieves cost reduction and emission mitigation by optimally coordinating PV energy generation, grid electricity usage, EV charging schedules, and hydrogen production. Results confirm that the proposed methodology effectively achieves cost reduction and emission mitigation by optimally coordinating PV energy generation, grid electricity usage, EV charging schedules, and hydrogen production. According to the results, a 21.63% saving was achieved in carbon emissions and carbon tax.